Grassroots informatisation: the internet and everyday information seeking practices in rural and urban China - Yan, P (2019)
Contemporary China has seen a proliferation of Information and Communication Technologies (ICTs). Part of this transformation is that mobile technologies have rapidly become widely used among rural and working-class Chinese populations. Meanwhile, the dichotomy between online and offline has become less distinct compared to the early years of Internet development, leading to a convergence between the Internet and traditional sources of information. Previous research on these topics has primarily focused on the Internet’s disruptive role in challenging the Chinese authority of Party- state or on the co-evolution of Chinese civil society and government. However, it is unclear without substantial empirical evidence how the rapid development of ICTs has influenced the routine and mundane lives of ordinary Chinese people. These routine practices, however, are fundamental to understanding the impact of the Internet on Chinese society and economy. The study of information practices in everyday life offers a way to understand how ICTs complement or displace traditional information sources. Instead of studying savvy Chinese Internet users in major cities, this research aims to understand how the Internet fits into the everyday lives of rural and working-class Chinese users. Through extensive fieldwork in Central China, this research studies how rural and working-class users have adapted to digital technologies, how ICTs satisfy or fail to meet daily information needs, and whether digital technologies have caused disruptions in information seeking practices. The research takes a bottom-up perspective in studying how the Internet is embedded in everyday information seeking practices. In terms of methods, the research employs both a quantitative approach including surveys and qualitative data such as interviews and focus group studies. By detailing how the Internet changes information seeking practices in everyday life, the thesis contributes insights to understanding the challenges and opportunities brought about by various social divides and divides in information seeking practices.